Ground reaction force and cadence during stationary running sprint in water and on land - De Brito Fontana H.* (2015)
This study was aimed at analyzing the cadence (Cadmax) and the peak vertical ground reaction force (Fymax) during stationary running sprint on dry land and at hip and chest level of water immersion. We hypothesized that both Fymax and Cadmax depend on the level of immersion and that differences in Cadmax between immersions do not affect Fymax during stationary sprint. 32 subjects performed the exercise at maximum cadence at each immersion level and data were collected with force plates. The results show that Cadmax and Fymax decrease 17 and 58% from dry land to chest immersion respectively, with no effect of cadence on Fymax. While previous studies have shown similar neuromuscular responses between aquatic and on land stationary sprint, our results emphasize the differences in Fymax between environments and levels of immersion. Additionally, the characteristics of this exercise permit maximum movement speed in water to be close to the maximum speed on dry land. The valuable combination of reduced risk of orthopedic trauma with similar neuromuscular responses is provided by the stationary sprint exercise in water. The results of this study support the rationale behind the prescription of stationary sprinting in sports training sessions as well as rehabilitation programs.